2017
DOI: 10.1002/tee.22481
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the parameters of neural mass models including time delay and nonlinearity using a particle filter: a preliminary study toward model‐based EEG analysis

Abstract: Electroencephalogram (EEG) and local field potential (LFP) signals are measured for both experimental and clinical purposes which include sleep stage analyses, brain–computer interfaces, and disease diagnosis. EEG and LFP data analyses are typically based on models assuming that the measured data is generated from a biological system and estimate the model parameter values that most accurately reproduce the measured data. Thus, use of a biologically plausible model is important for a model‐based analysis. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The mean value and the standard deviation were 0.077 s and 0.00449 s, respectively. This result is consistent with those from with previous studies where t 0 was estimated with other methods such as curve fitting [22,23,27] or particle filter [24] and supports the validity of our method based on Eq. (8).…”
Section: Delay Of the Cortico-thalamo-cortical Loopsupporting
confidence: 93%
See 3 more Smart Citations
“…The mean value and the standard deviation were 0.077 s and 0.00449 s, respectively. This result is consistent with those from with previous studies where t 0 was estimated with other methods such as curve fitting [22,23,27] or particle filter [24] and supports the validity of our method based on Eq. (8).…”
Section: Delay Of the Cortico-thalamo-cortical Loopsupporting
confidence: 93%
“…(4) and (1). In this study, M was set to 10 by using t 0 ≅80 ms, which was shown in previous studies [22,23,24,27], and T s =1/128 Hz. The RTF for the AR model is expressed as The same procedure that was used to derive Eq.…”
Section: Analytical Methods To Estimate Cortico-thalamo-cortical Loop mentioning
confidence: 99%
See 2 more Smart Citations